2012
DOI: 10.1007/s10620-011-2012-4
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Prevents the Induction of iNOS Gene Expression Through Destabilization of Its mRNA in Proinflammatory Cytokine-Stimulated Hepatocytes

Abstract: Results indicate that α-LA inhibits the induction of iNOS gene expression at a posttranscriptional step via iNOS mRNA stabilization, rather than promoter activation. It may provide useful therapeutic effects through the suppression of iNOS induction involved in liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Yamada et al suggested that LA inhibits the induction of iNOS gene expression at a posttranscriptional step via iNOS mRNA stabilization, which results in decreased production of NOx. 36 According to these studies, this could be possible mechanism by which LA decreased NOx level in all examined brain regions in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Yamada et al suggested that LA inhibits the induction of iNOS gene expression at a posttranscriptional step via iNOS mRNA stabilization, which results in decreased production of NOx. 36 According to these studies, this could be possible mechanism by which LA decreased NOx level in all examined brain regions in our study.…”
Section: Discussionsupporting
confidence: 57%
“…As a support to this earlier reported study, we noted that pretreatment of ALA could effectively reduce LPS-induced COX-2 expression and PGE2 synthesis in rat mesangial cells. In addition, Yamada and coworkers (2012) have shown that ALA destabilizes the mRNA of iNOS gene and consequently reduces its expression in pro-inflammatory cytokine-stimulated hepatocytes [40]. Because selective inhibition of iNOS is a potential treatment for sepsis-induced AKI [41], we hypothesized that suppression of iNOS induction underlay the protective effects of ALA in this disease.…”
Section: Discussionmentioning
confidence: 94%
“…This could be caused by inhibition of an inducible isoform of NOS expression by α-lipoic acid through destabilization of its mRNA, resulting in decreased NO production [35]. The excess NO reacts with the superoxide anion to produce peroxynitrite (ONOO - ), which can induce mitochondrial dysfunction, lipid and protein oxidation [28].…”
Section: Discussionmentioning
confidence: 99%